PENGARUH KERAGAMAN PRODUK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DAN MINAT BELI KONSUMEN SEBAGAI VARIABEL INTERVENING PADA TOKO MELINA PANJI SITUBONDO - Zein, Achmad Faried; Karnadi, Karnadi; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Currently, the global industrial world is entering a new era known as the Industrial Revolution 4.0, where in this era the competition in the world of trade is getting tighter so that free trade is starting to emerge. To overcome the emergence of free trade, Indonesia needs real preparations, one of the strategies carried out by the government is the Strengthening of the SME Sector (Rachmat, et al., 2016). Strengthening this sector will run optimally if modern marketing concepts are added by setting consumers as the main concern. Therefore, to attract consumers' buying interest, SMEs must increase their creativity and be good at seeing market share opportunities. SMEs are said to be successful in trading competition when they can maintain customer buying interest through product marketing. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that product diversity has a significant positive effect on consumer buying interest. Product quality has a significant negative effect on purchasing decisions. Product Diversity and Product Quality have a significant positive effect on Consumer Buying Interest. Consumer Buying Interest has a significant positive effect on Purchase Decisions. Product Diversity on Consumer Buying Interest through Purchase Decisions has a significant positive effect. Product Quality on Consumer Purchase Interest through Purchase Decision has a positive but not significant effect.